Nigerian Biofuels Policy and Large-Scale Land Acquisitions: Implications for Food Security - Echa Attah, Noah (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This paper examines, based on empirical investigations, the overall implications on food security of the proliferation of biofuels production and large-scale land acquisitions against the background of Nigeria being food import dependent and a leading producer of fossil fuel. It focuses on how the cultivation for fuel, of crops such as cassava, corn and sorghum (major staple foods), oil palm, sugar cane and jathropha (a non-food crop) affect food security as food and fuel compete for land use. The food versus fuel debate is reviewed within the context of Nigeria, without necessary relying on the global generalization. Similarly, the theory of “unintended consequences” is adopted for the study. Data on designated fuel crops and biofuels policy are used to examine the nature, direction, pace, and drawing the nexus between biofuels production and land grabbing and their impacts on food security in Nigeria. The data is collected through semi-structured questionnaires, interviews, focused group discussions with targeted stakeholders and secondary data from policy documents. The result of the study reveals the effect of Nigerian biofuels policy and large-scale land acquisitions on food security in Nigeria.